Insights into Early Identification of Oral Potentially Malignant Disorders and Oral Cancer-A Cross-Sectional KAP Study among Dentists - Yeladandi, Mounika; Uma Maheswari, Thirupambaram Nataraja Sundaram; Neelam, Shivani; Chaitanya, Nallan CSK; Vemula, Harika; Kala, Tejaswi; Abidullah, Mohammed (International Journal of Pharmaceutical Investigation, 2025)
Background: Oral cancer, including malignancies of the oral cavity and associated structures, poses a significant global health challenge. Early identification is crucial for improving treatment outcomes and survival rates. This study evaluated the Knowledge, Attitudes and Practices (KAP) of dental professionals in Hyderabad, Telangana, regarding the early detection of oral premalignancies and oral cancer. A cross-sectional study was conducted among 384 dental professionals using a 24-item questionnaire covering demographics, knowledge, attitude and practice components. Data collection took place in dental clinics and statistical analyses were performed using descriptive statistics, frequency distribution and Chi-square tests, with p<0.05 considered significant. Results: Among 384 surveyed professionals, 67% demonstrated commendable knowledge, 81% had a positive attitude and 58% engaged regularly in screening and diagnosing oral cancers. Professionals over 35 years scored higher in practice-related aspects, yet only 42.4% were familiar with using screening devices and 29.8% routinely performed diagnostic activities. While knowledge and attitudes were generally favorable, practical implementation, especially among younger dentists, needs improvement. Conclusion: The findings emphasize the need for targeted training and educational programs to enhance practical skills, including the use of diagnostic tools. Integrating oral cancer education into dental curricula may further encourage proactive attitudes and practices, improving early detection and patient outcomes.
Keywords: Dental Professionals; Early Detection; Oral Cancer; Premalignant Lesions; Screening Devices